Study of the Implementation of the Occupational Safety and Health Management System (SMK3) in Construction Work Companies in the City of Manado - Leidy Magrid Rompas; Steven Lintong; Theo Kurniawan Sendow (PT FORMOSA CENDEKIA GLOBAL, 2024)
Occupational Safety and Health (K3) is crucial for companies with high risks of workplace accidents, particularly those involved in construction work. However, many workplace accidents still occur due to inadequate implementation of the Occupational Safety and Health Management System (SMK3). This situation may be influenced by several contributing factors. A comprehensive literature review of previous studies was conducted to identify the factors contributing to the poor implementation of SMK3 in construction companies. The findings suggest that the key factors include compliance with legal regulations, commitment to K3 policies, human and environmental factors, financial constraints, and government support. Based on these findings, a study on the implementation of the Occupational Safety and Health Management System (SMK3) in construction companies in Manado is necessary